2022
DOI: 10.1177/00952443221077438
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different cure systems on natural rubber/nanocellulose nanocomposites in rheological, physical-mechanical, aging, and mechanical properties

Abstract: The effect of different crosslink structures was studied in nanocomposites obtained by co-precipitation of natural rubber (NR) latex and aqueous solution of cellulose xanthate for obtaining nanocellulose. Cure systems characterized as conventional (CV), semi-efficient (SEV), and efficient (EV) were used in compositions of NR and also in natural rubber/cellulose (NR/CEL) nanocompositions with 15 phr of cellulose. The characterization of the developed compositions was based on rheological, physical-mechanical, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…In the study conducted by Ceren and Yunus [15], a blend film was prepared by blending a natural rubber derivative containing acetate pendant groups (ANR) with PLA. The research results showed that the blend exhibited the best compatibility with PLA when the ANR content was 25wt%.…”
Section: Blending Modification Of Plamentioning
confidence: 99%
“…In the study conducted by Ceren and Yunus [15], a blend film was prepared by blending a natural rubber derivative containing acetate pendant groups (ANR) with PLA. The research results showed that the blend exhibited the best compatibility with PLA when the ANR content was 25wt%.…”
Section: Blending Modification Of Plamentioning
confidence: 99%
“…According to the ratio of sulfur/accelerator (S/A), it could be divided into common conventional (CV), semi-effective (SEV), effective (EV) systems [29][30][31]. Honorato et al investigated the different crosslink structures in in uencing the mechanical properties of NR composites, which demonstrated that CV system had the well-developed crosslink networks and improved tear strength through Penny effect and Gibbs free energy method [32]. Larpkasemsek and co-workers also demonstrated the highest crosslink density with CV system owned the good mechanical properties and the fastest vulcanized rate for epoxied NR composites [33].…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that the polymer matrix next to CB particles can accelerate the reconstruction of the filler–polymer network, thereby enhancing the reversibility of the Payne effect [ 12 , 13 , 14 ]. CB, along with other fillers, such as spherical [ 15 , 16 , 17 ] and fibrous [ 18 , 19 , 20 ], have excellent electrical and thermal conductivity, which significantly affects Payne effect improvement. Experimental research can satisfactorily explain the Payne effect of mixed rubber filling.…”
Section: Introductionmentioning
confidence: 99%